Editorial: Looking Back, Looking Forward: The UN Trafficking Protocol at fifteen - Bhabha, Jacqueline (Anti-Trafficking Review, 2015)
Anniversaries provide a pretext for reflection—celebration for national independence days, mourning for war-time massacres. For political reforms and legal innovations, anniversaries warrant a different set of reflections: less predictable or uniform, more sober stock taking and weighing of achievements and failures than affirmation of unequivocal success or defeat. This fourth special issue of the Anti-Trafficking Review embraces the occasion of the fifteenth anniversary of the 2000 United Nations (UN) Protocol to Prevent, Suppress and Punish Trafficking in Persons, Especially Women and Children (hereafter Trafficking Protocol), and evaluates the impact of this landmark instrument of international law on the grave social, political and economic problems it targets. Among the many and varied constituencies concerned with issues of trafficking, from government bodies to international advocacy groups to sex worker collectives, the Trafficking Protocol has attracted considerable attention. It has been widely ratified, its definition of trafficking has been extensively invoked, its criminalisation mandates have been aggressively followed, its victim protection measures have been enthusiastically cited.